INFLUENCE OF SOCIO-ECONOMIC FACTORS ON THE INCOME OF FEMALE EMPLOYEES' FAMILIES PT. SOCFINDO SEUNAGAN PLANTATION (DIVISION 2) - Tuti Safrina; Devi Agustia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study was to determine socioeconomic factors in increasing family income of female employees at PT. Socfindo kebun seunagan, the decision of female employees to work is to help increase income in the household in order to get a better life in the future. The determination of the place of research was carried out in a deliberate way (purposive), namely at PT. Socfindo garden seunagan. The determination of research was done by means of surveys or interviews with the number of respondents as many as 30 people. The results showed that based on the results of the T count from this study that only three variables had an effect on increasing income, namely the outpouring of working hours, family dependents, and age while the education variable did not affect the income of female employees at PT. Socfindo Seunagan Garden. Based on F count obtained F Table 2.587. where if F calculates > from F table can affect between working hours, the number of family dependents, age, and education affect the income of female employees at PT. Socfindo Seunagan Garden.